Atlas of Fine Needle Aspiration Cytology - Domanski, Henryk A.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
This book covers all of the diagnostic areas where FNAC is used today. This includes palpable lesions and lesions sampled using various radiological methods, and correlations with ancillary examinations detailed on an entity-by-entity basis. As well as being a complete atlas of the facts and findings important to FNAC, this atlas is a guide to diagnostic methods that optimize health care. The interaction of the cytologist or cytopathologist with other specialists (radiologists, oncologists and surgeons) involved in the diagnosis and treatment of patients with suspicious mass lesions is emphasized and illustrated throughout.   With contributions from experts in the field internationally and abundant colour images Atlas of Fine Needle Aspiration Cytology provides a comprehensive and up-to-date guide to FNAC for pathologists, cytopathologists, radiologists, oncologists, surgeons and others involved in the diagnosis and treatment of patients with suspicious mass lesions.
Introduction -- Image-Guided Fine Needle Aspiration Cytology -- Breast -- Head and Neck: Salivary Glands -- Thyroid -- Lung -- Mediastinum and Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration -- Lymph Nodes -- Spleen -- Liver -- Pancreas -- Kidney and Adrenal Gland -- Soft Tissue -- Skin and Subcutis -- Bone -- Pediatric Tumours -- Orbit and Ocular Adnexa.
Keywords: Pathology; Pathology